2005
DOI: 10.2736/jjvd.11.9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A three-month-old, female Cairn terrier presented with dermatitis on the periocular areas and lower jaw. Histopathologic examination was performed, and this dog was diagnosed as having Juvenile cellulitis. Although cephalexin and ketoconazole which were used prior to skin biopsy, were not effective, skin lesions were completely improved one month later with oral griseofulvin 20 mg/kg BID as immunoregulatory therapy.(Jpn J Vet Dermatol 2005, 11 (1): 9-12)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The outcome could have been favorable if the treatment proposed had been instituted. Some authors have reported other satisfactory therapeutic options, including griseofulvin used as an immunomodulatory drug, and the combination of prednisolone with cyclosporine (MIURA et al, 2005;PARK et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome could have been favorable if the treatment proposed had been instituted. Some authors have reported other satisfactory therapeutic options, including griseofulvin used as an immunomodulatory drug, and the combination of prednisolone with cyclosporine (MIURA et al, 2005;PARK et al, 2010).…”
Section: Discussionmentioning
confidence: 99%